POTENSI PENGEMBANGAN EKOWISATA DI DESA PELIATAN, KECAMATAN UBUD, BALI - Adnyana, I Nyoman Gede Wisesa; Ginantra, I Ketut; Astarini, Ida Ayu (SIMBIOSIS, 2020)
The purpose of this study is to find out the potential of Peliatan Village to be an ecotourism village and the eligibility of Peliatan Village to be an ecotourism destination. Four aspects were observed. They weare attraction, accessibility, amenity and ancillary. The method used to get the data are deep-interview with the Head of Peliatan Village, locals, and visitors, literature review, observation and accidental questionnaire. Data analysis was done by scoring and description. The result of the observation shows that Peliatan Village has the potential relating to the natural attraction e.g. the diversity flora and wild animals, ecosystem of rice field and river, cultural attraction, man-made attraction, accessibility, amenity, ancillary and society's participation in the development of ecotourism village. Peliatan Village is eligible to be expanded into an ecotourism area based on the five criteria of ADO-ODTWA with eligibility index of 96.11%. Keywords: attraction, destination eligibility, flora fauna , sustainable tourism.